Epidemiological Profile of Children with Malnutrition at Child Malnutrition Treatment Center (CMTC) in Saurashtra Region - Dhara N. Jahangirporia; Chikitsa D. Amin; Amiruddin M. Kadri (Indian Association of Preventive and Social Medicine, 2023)
Introduction: Adequate Nutrition is important for optimum growth, immunity, neurological and cognitive development of the child. Malnutrition leads to illness and mortality among under 5 children. Nearly 40% under 5 children are malnourished in Gujarat despite many nutritional programmes. Objectives: To assess the epidemiological factors of malnourished children at Child Malnutrition Treatment Centre (CMTC) and to find out the association between epidemiological factors and nutritional status of study participants. Method: A single centric, cross-sectional study was conducted on Children admitted at CMTC at Narayan Nagar Urban Health Center, the only one and newly established CMTC in Rajkot city in year 2015. Study duration was 14 months. Interview of mothers of 120 children was conducted to know epidemiological factors of malnourished children. Weight on admission was noted from register. Pre-formed, semi-structured proforma used. Results: Out of 120 children, 5.8%, 55.8%, 34.2% and 4.2% were from <1, 1-3, 3-5 and >5 year age groups respectively. Nearly 40% children belonged to Socioeconomic Class IV. The proportion of Low Birth Weight children was 40%. Current feeding practice was appropriate in 10.8% children according to IMNCI guideline. Upper Respiratory Tract Infection occurred in 76.7% children with average 4.5 episodes. High birth order of children is statistically significant with severity of malnutrition. Birth weight and feeding practices of children were not associated with grade of malnutrition. Conclusion: Need based education of mothers for preventing low birth weight, exclusive breastfeeding, complementary feeding, quantity and type of routine diet etc. should be given.